Analytical method for forces between current carrying infinite bars. Issue 3 (3rd May 2016) - Compter, John; Giaccone, Luca
Abstract : Purpose: – The purpose of this paper is to calculate forces between rectangular conductors with a uniform current density as can be found in the long coils as used in linear actuators and planar motors. Design/methodology/approach: – The proposed methodology relies on a single analytical equation that is used to compute all the force components. Findings: – Several comparisons with other available techniques are provided. All the comparisons confirm the validity of the proposed analytical method. Originality/value: – In the literature, other analytical methods for the force computation can be found. However, these often have limitations (e.g. only adjacent conductors or non-adjacent conductors). This paper adds a new compact expression that covers all the possible configurations at the same time. This new tool holds for all the analytical expression found in the literature.